ALAT MONITORING DAN PENGENDALI SAKLAR PERALATAN LISTRIK JARAK JAUH - Sindy Sindy; Chairisni Lubis; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This design, use the mobile phone as a controller and microcontroller as a central control system. Microcontroller will be executed on the orders received from the modem which connected to the microcontroller. Several types of sensors are used to monitor them, such as LDR sensors to detect light, LM35 sensor to detects the room temperature and the MQ-2 sensor to detect gas leaks.    The test results show that the system is already capable of controlling electrical equipment and monitor the lights and temperature conditions. In addition, the system can report a gas leak and fire to the phone number that has been saved.